Critical-progressive Muslim thougth : Reflection on its political ramifications - Duderija, A. (Routledge, 2013)
Many of the contemporary political conflicts in Muslim-majority countries are said to pit modern secularists against the “backward” Islamists. However an important stream of contemporary Muslim thought—critical-progressive Muslim thought—refuses to accept either a hegemony of Western secularism or a hegemony of Islamist fundamentalism. Critical-progressive Muslim scholar-activists are reinterpreting the normative teachings of the Muslim worldview and developing a distinctive third-way approach. There are several key political and policy ramifications of this stream of thought, including a robust commitment to religious freedom, but within Islamic terms, not terms dictated by non-Muslim Westerners preoccupied with their own security interests.